The Difference Between Spiritual Emotional Freedom Technique And Acupressure On The Dysmenorrhea Intensity - Wulandari, Priharyanti; Nurmadinisia, Rahmi; Nurdiana, Dina (IAKMI South Tangerang Branch, 2025)
Background: Dysmenorrhea is a type of menstrual pain that is often experienced by adolescent girls, including school-aged students. This condition can interfere with learning activities, concentration, and even psychological well-being, often leading to school abstain. Method: This study employed used a non-equivalent control group design. Proportional stratified random sampling was conducted on 110 students at SMP Plus Cahaya Insan Depok who met the inclusion criteria. Pain intensity was measured using the Numeric Rating Scale (NRS). Data were analyzed using the Wilcoxon Sign Rank Test and the Mann-Whitney test. Results: The results showed that the average value of pain intensity in the intervention group (SEFT) was 4.95 which decreased to 2.11, showing a difference of 2.84. Meanwhile, the average value in the control group (acupressure) was 4.65 which decreased to 4.00, showing a difference of 0.65. There was a significant difference in the average dysmenorrhea intensity between the SEFT group and the acupressure group after treatment, with a p-value of 0.002 (<0.05). Conclusion: There is a significant difference in the effect of SEFT and acupressure on dysmenorrhea among adolescent girls.